Input-output state feedback linearization and model predictive control of an MSMPR crystalliser [Abstract] - R. Parekh; Brahim Benyahia; Chris Rielly (2017)
Input-output state feedback linearization and model predictive control of an MSMPR crystalliser [Abstract]